The research for partitioned algorithm of coupling of elastic pipe and cross-flow in a cylinder - Qian Bei Yue (Journal of Vibroengineering, 2017)
In the marine flatbed, nuclear power stations and oil fields, the marine risers and heat exchangers are induced vibrations and collision, even caused failure with cross flow. This is a typical problem of bundles vibration in fluid-structure interaction. In this paper, the elastic pipe was separated into several beam elements. And the dynamical equation was adopted to describe the structure. The fluid domain of cylinder was separated into solid elements. And the computational fluid dynamics equation was adopted to describe the fluid. At the fluid-structure coupling interface, the formulas of displacement, velocity and load was derived and the corresponding convergence criterion was also derived. Thus, the partitioned coupling algorithm was established for the elastic pipe and the cross-flow in cylinder. The example showed that, comparing to the results of monolithic coupling algorithm, the error was small. Thus, it proved that the correctness of the partitioned coupling algorithm in this article. And it will provide an effective computational method for vibrations and collision of bundles in a more complex fluid domain.